Handbook of mechanical alloy design - Totten, George E; Xie, Lin; Funatani, Kiyoshi (Mechanical engineering, 2004)
Basic principles - Risk-based metallurgical design - Designing with carbon, low and medium alloy steels - Designing with tool steel - Designing with high-strength low alloy steels - Designing with microalloyed and interstitial-free steels - Designing with stainless steel - Cast iron design: processes, alloys and properties - Designing with aluminum alloys - Designing with magnesium: alloys, properties and casting processes - Designing with titanium alloys - Designing with ni-base alloys - Designing with copper alloys - Designing with powder metallurgy alloys - Designing with metal-matrix composites.